PENGARUH LABEL HALAL TERHADAP MINAT BELI KOSMETIK PERAWATAN DAN RIASAN PADA MAHASISWI PRODI PENDIDIKAN TATA RIAS DAN KECANTIKAN JURUSAN KESEJAHTERAAN KELUARGA FAKULTAS TEKNIK UNIVERSITAS NEGERI PADANG - Yasnita, Yasnita; Rostamailis, Rostamailis; Hayatunnufus, Hayatunnufus (Journal of Home Economics and Tourism, 2015)
This study aims to see whether there is an influence of ‘halal’ labelon buying interest by the students of Education Makeup and BeautyFaculty of Engineering Department of Padang State University. Thisresearch is descriptive quantitative. The populations in this research were137 female students and the sample about 102 female students ofEducation Makeup and Beauty Faculty of Engineering Department ofPadang State University in academic year 2010 to 2013. The research datais primary data that obtained directly from the respondents in the form 43items questionnaire with a number of statements by using Likers scale thathas been tested for validity and reliability. Data were analyzed usingdescriptive analysis that was performed linearly test, normality test andhypotheses test with product moment correlation. The results showed thatthere was no significant relationship but it has a positive side between‘halal’ labels on buying interest. The analysis showed that the ‘Halal’Label located on the percentage of 55% in a low category, and InterestBuy obtained the percentage 81% in a high category.Keyword: Halal label, buying interest cosmetic care and makeup